Surveillance of stroke: a South-East Asia Region (SEAR) perspective - Yogeshwar V. Kalkonde; Sukanya Rangamani; Nijasri C. Suwanwela; Prashant Mathur; Ranjit J. Injety; Ivy A. Sebastian; Pranay J. Vijayanand; Nistara S. Chawla; P.N. Sylaja; Meenakshi Sharma; Jeyaraj D. Pandian (Elsevier, 2023)
Summary: Surveillance of stroke is critical to track its burden and assess progress in prevention and treatment. We reviewed the literature to evaluate stroke surveillance efforts in the South-East Asia Region (SEAR) countries, identify progress and assess gaps. Epidemiological data on all the major parameters such as the incidence, prevalence and mortality of stroke were available for India and Thailand but for none of the other SEAR countries. Most of the epidemiological data came from investigator-initiated studies. National stroke surveillance was present only in India in the form of a National Stroke Registry Programme and Thailand has a national database that was used to obtain epidemiological data for stroke. Research on novel methods for stroke registration, such as using information technology, was absent. This review identified serious gaps in the monitoring and surveillance of stroke in SEAR countries. Systematic efforts are needed to fill those gaps.